PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN PADA RUMAH SAKIT UMUM DAERAH (RSUD) Dr. MOHAMAD SALEH KOTA PROBOLINGGO - Fina oktavia, Fina Oktavia; Astuti, Veronica Sri; Busthomi, Ach. Noor (Universitas Panca Marga, 2023)
The purpose of this research is to know the Effect of Service Quality of PatientSatisfaction At The Regional General Hospital (RSUD) dr. Mohamad Saleh City of Probolinggo. This type of research used in this paper is an explanatory method, a study that explain or describe something, which aims to test hypotheses regarding the causal relationship between the variables studied. While the data collection methods quantitative conducted with survey approach. The survey was a quantitative research that is equal to many people and then all of the answers obtained by researchers recorded, processed, and analyzed. The number of samples used was 100 patients and the data was collected using a questionnaire with a Likert scale which was distributed to patients as respondents. The results of the analysis of this study indicate that based on the results of the regression of service quality (X) of 33.037, it indicates that the results of the assessment of service quality are pure without being influenced by independent variables. while the regression value of Service Quality (Y) is 0.362 indicating a positive contribution is generated by Service Quality, meaning that if Service Quality is increased by 1 point it will affect Service Quality by 0.362. In other words, the better the quality of service, the patient satisfaction will increase.